Hedge algebras, the semantics of vague linguistic information and application prospective - Nguyen, Cat Ho; Tran, Thai Son; Vu, Nhu Lan (Vietnam Journal of Science and Technology, 2016)
The report aims to show that hedge algebras model actually the proper qualitative semantics of words of linguistic variables based on the argument that the inherent qualitative semantics of words should be expressed through the order relationships, induced by the word semantics, between the words in their respective variable domains, as required by decision making of human daily lives. This makes the hedge algebra based approach to the word semantics quite different from the existing approaches and become the only approach that can immediately deal with the natural qualitative semantics of words. We explain clearly and systematically distinguished features and properties of this approach to show that these seem to make the approach to be sound and ensure its effectiveness in applications. This approach seems to be promising for development of hedge algebra-based method to solve problems in various application fields. For illustration, we will give a short overview of effective results some of the initial applications of hedge algebras in the fields of knowledge based systems and in fuzzy control.